2016
DOI: 10.18632/oncotarget.9669
|View full text |Cite
|
Sign up to set email alerts
|

Opposite prognostic roles of HIF1α and HIF2α expressions in bone metastatic clear cell renal cell cancer

Abstract: BACKGROUNDPrognostic markers of bone metastatic clear cell renal cell cancer (ccRCC) are poorly established. We tested prognostic value of HIF1α/HIF2α and their selected target genes in primary tumors and corresponding bone metastases.RESULTSExpression of HIF2α was lower in mRCC both at mRNA and protein levels (p/mRNA/=0.011, p/protein/=0.001) while HIF1α was similar to nmRCC. At the protein level, CAIX, GAPDH and GLUT1 were increased in mRCC. In all primary RCCs, low HIF2α and high HIF1α as well as CAIX, GAPD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 28 publications
1
13
0
Order By: Relevance
“…Currently, several biomarkers for KIRC that have been detected include von Hippel-Lindau (VHL) [ 8 11 ], vascular endothelial growth factor (VEGF) [ 12 15 ], carbonic anhydrase IX (CAIX) [ 16 18 ], and hypoxia-inducible factor 1 alpha/2 alpha (HIF1a/2a) mutations [ 19 21 ], some of which were able to forecast the medical effectiveness and outcomes. Despite that, there have been scarce studies into the molecular biomarkers of KIRP for the prediction of therapeutic efficacy and prognostication.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, several biomarkers for KIRC that have been detected include von Hippel-Lindau (VHL) [ 8 11 ], vascular endothelial growth factor (VEGF) [ 12 15 ], carbonic anhydrase IX (CAIX) [ 16 18 ], and hypoxia-inducible factor 1 alpha/2 alpha (HIF1a/2a) mutations [ 19 21 ], some of which were able to forecast the medical effectiveness and outcomes. Despite that, there have been scarce studies into the molecular biomarkers of KIRP for the prediction of therapeutic efficacy and prognostication.…”
Section: Introductionmentioning
confidence: 99%
“…A total of 38 from the selected 49 studies investigated the association between HIF-2α and OS. All the necessary information to estimate the HR could not be obtained from two papers and were therefore not included in the analysis (Table S1 in Supplementary Material) ( 21 , 23 , 24 , 26 31 , 33 35 , 37 – 39 , 41 43 , 45 , 46 , 48 , 49 , 51 , 52 , 54 – 57 , 59 , 60 , 62 69 ). Based on these studies, high HIF-2α expression was statistically significantly associated with a decreased OS (HR = 1.69, 95% CI 1.39–2.06, p < 0.0001, Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…We found that the pooled HR for MFS was 2.67 (95% CI 1.32–5.38, p = 0.0061), indicating that HIF2α expression is a negative prognostic factor for MFS in patients with prostate and salivary gland cancer (Figure 7 ). In kidney cancer, one paper reported an inverse correlation between HIF-2α positivity and MFS (HR = 0.08, 95% CI 0.03–0.27, p < 0.001) ( 23 ).…”
Section: Resultsmentioning
confidence: 99%
“…Many lines of evidence suggest that the expression level of HIF2a was enhanced and predicted poor survival in a variety of cancers, (32). Conversely, some studies have indicated that HIF2a have a significant impact on the development of tumors, and increased HIF2a expression could be a favorable prognostic factor in RCC (43) and HCC (21). Moreover, clinicopathologic significance of HIF2a in cancer patients remains inconclusive.…”
Section: Discussionmentioning
confidence: 99%